2008
DOI: 10.18637/jss.v026.i03
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary PrecisionMathematicaFunctions to Evaluate the One-Sided One Sample K-S Cumulative Sampling Distribution

Abstract: Efficient rational arithmetic methods that can exactly evaluate the cumulative sampling distribution of the one-sided one sample Kolmogorov-Smirnov (K-S) test have been developed by Brown and Harvey (2007) for sample sizes n up to fifty thousand. This paper implements in arbitrary precision the same 13 formulae to evaluate the one-sided one sample K-S cumulative sampling distribution. Computational experience identifies the fastest implementation which is then used to calculate confidence interval bandwidths a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…In order to determine the normality interval we use the Kolmogorov-Smirnov normality test [ 31 , 32 ], which is the most usual empirical distribution function test for normality.…”
Section: Methodsmentioning
confidence: 99%
“…In order to determine the normality interval we use the Kolmogorov-Smirnov normality test [ 31 , 32 ], which is the most usual empirical distribution function test for normality.…”
Section: Methodsmentioning
confidence: 99%
“…several opportunities to lose accuracy: in the addition/subtraction, the exponentiation, and the multiplication, before considering the summation. Brown and Harvey [17] go into quite some detail on the precision required for internal computations in order to achieve a desired accuracy in the final result. The magnitude of the terms in Eq.…”
Section: Controlling Accuracy Lossmentioning
confidence: 99%
“…Computing S n ( k n ) in this manner loses about 1.6 * (k− 1) bits. Brown and Harvey [17] analyzed the extra internal digits of precision needed to compute using Formula 31. They found that the number of extra digits needed grows like O( √ n) (keeping the p SF fixed and evaluating at x n = S −1 n (p SF )).…”
Section: Evaluation Near X=0mentioning
confidence: 99%
“…Drew Glen & Leemis [14] generated the collection of polynomial splines for n <= 30. Brown and Harvey [15,16,17] implemented several algorithms in both rational arithmetic and arbitrary precision arithmetic. Simard and L'Ecuyer [18] analyzed all the known algorithms for numerical stability and sped.…”
Section: Review Of Kolmogorov-smirnov Statisticsmentioning
confidence: 99%